Construction of a well-dispersed Ag/graphene-like g-C3N4 photocatalyst and enhanced visible light photocatalytic activity. Issue 14 (27th January 2017) - Li, Hao; Jing, Yue; Ma, Xinlong; Liu, Tongyao; Yang, Linfeng; Liu, Bin; Yin, Shu; Wei, Yongzhi; Wang, Yuhua
Abstract : A Ag/graphene-like g-C3 N4 photocatalyst was synthesized via a simple thermal oxidation exfoliation-photodeposition technique. Abstract : In order to overcome the intrinsic drawback of pristine g-C3 N4, we demonstrate a simple thermal oxidation exfoliation-photodeposition technique to fabricate a Ag/graphene-like g-C3 N4 (Ag/G-g-C3 N4 ) photocatalyst. It was revealed that the monodispersed Ag nanoparticles were well dispersed on the surface of graphene-like g-C3 N4 (G-g-C3 N4 ). The Ag/G-g-C3 N4 displayed an enhanced photocatalytic activity for methylene blue degradation and the degradation rate was 10 times higher than that of pristine g-C3 N4 under visible light irradiation. The enhancement of photocatalytic activity could be attributed to the surface plasmon resonance effect of Ag and large surface area (189.9 m 2 g −1 ) of G-g-C3 N4, which improve the visible light absorption ability and provide abundant reactive sites as well as promoting photogenerated electron–hole pair separation.